Community Participation and Empowerment in a Post-disaster Environment: Differences Tied to Age and Personal Networks of Social Support - Marenco-Escuderos, Ailed Daniela; Ramos-Vidal, Ignacio; Palacio-Sañudo, Jorge Enrique; Rambal-Rivaldo, Laura Isabel (Frontiers in Psychology, 2020)
In this article, an attempt was made to identify the level of community social participation according to age, gender and the structural characteristics of the personal support networks in a population displaced by floods in the Colombian Caribbean. The research was based in a non-experimental methodology with an associative-relational strategy. An intentional non-probabilistic sample of 151 people affected by the winter wave in the south of the Department of Atlántico (Colombia) was selected. In total, the study included 42 males (27.8 %) and 109 females (72.2 %) participants, with an average age of 37.48 (±14, Range 18 - 80) and average relocation time of 21.79 months (± 8.22, Range 5-36). The Arizona Social Support Interview Schedule (ASSIS) and Community Empowerment instruments were responded to with an instrument adapted from the leadership competence factor. The results show lower rates of intermediation in the older population, and the relationship between social participation and gender shows equally cohesive social support networks in men and women. This evidence is discussed to promote psychosocial interventions aimed to increase community engagement and empowerment of people that have experienced non-voluntary mobility processes.